1996
DOI: 10.1021/ef950197u
|View full text |Cite
|
Sign up to set email alerts
|

Reoxidation and Deactivation of Supported Cobalt Fischer−Tropsch Catalysts

Abstract: The role of water in the deactivation of Al2O3-supported cobalt Fischer−Tropsch catalysts has been studied at different water partial pressures. In addition, model studies at nonreacting conditions using H2O/H2 feeds were carried out in order to study the possible reoxidation of cobalt by water. High-pressure gravimetry, temperature-programmed reduction (TPR), and X-ray photoelectron spectroscopy (XPS) were used as characterization methods in the model studies. The kinetic studies showed significant deactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 17 publications
2
49
0
Order By: Relevance
“…Water decreased the reaction ate for all these catalysts. A negative impact on the Fischer-Tropsch activity for cobalt deposited on c-Al 2 O 3 due to addition of water is consistent with previous findings [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. It is known for similar catalysts that water may act as an oxidation agent, producing non-active cobalt.…”
Section: Narrow-pore Catalystssupporting
confidence: 91%
See 1 more Smart Citation
“…Water decreased the reaction ate for all these catalysts. A negative impact on the Fischer-Tropsch activity for cobalt deposited on c-Al 2 O 3 due to addition of water is consistent with previous findings [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. It is known for similar catalysts that water may act as an oxidation agent, producing non-active cobalt.…”
Section: Narrow-pore Catalystssupporting
confidence: 91%
“…Schanke et al [3,4] found that the presence of large amounts of water suppressed the activity of unpromoted as well as promoted cobalt supported on c-Al 2 O 3 . From X-ray photoelectron spectra, Schanke et al [3,4] concluded that reoxidation of surface cobalt atoms or highly dispersed cobalt phases, and not bulk cobalt oxidation, was responsible for the loss in activity. Hilmen et al [5][6][7] also observed a loss in activity when water was introduced to unpromoted and promoted cobalt deposited on c-Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of cobalt oxide on Si-B ended at less than 600°C, and most of the oxide species have been reduced in the first stage, whereas, the reduction of cobalt oxide on Si-A and Si-C were prolonged to much higher temperature, especially for Co/Si-C, the reduction didn't finished even at 1,173 K. In addition, Co/ Si-C has the largest area of the reduction peak in the second stage. It is believed that the second reduction stage is related to the reduction of amorphous cobalt oxide which interacts strongly with the support [19][20][21][22][23]. Thus, we conclude that Si-C interacts more strongly with the supported cobalt oxide.…”
Section: Catalytic Activity Evaluationmentioning
confidence: 67%
“…Figure 6 displays the H 2 -TPR profiles of the silica supported cobalt oxide catalysts. The reduction of supported cobalt oxide was generally divided into two stages [19][20][21][22][23], namely, the reduction of large crystalline Co 3 O 4 particles at lower temperature and the reduction of surface cobalt oxide species which interact strongly with the support at higher temperature. In our work, the reduction peaks below 773 K can be mainly resulted from the reduction of large Co 3 O 4 crystallites, which involves a two-step process of Co 3 O 4 to CoO and of CoO to Co, and the reduction of this stage is usually separated into two peaks.…”
Section: Catalytic Activity Evaluationmentioning
confidence: 99%
“…migration of small cobalt clusters or monoatomic species from small to large crystallites, is especially detrimental in FTS. This deactivation mechanism results in the creation of large crystallites but also very small cobalt clusters, the latter being particularly inactive in FTS [56][57][58] and prone to re-oxidation [59][60][61][62].…”
Section: Activity and Stability Of The Catalystsmentioning
confidence: 99%